2018
DOI: 10.1371/journal.pone.0191980
|View full text |Cite
|
Sign up to set email alerts
|

Patient navigators for people with chronic disease: A systematic review

Abstract: BackgroundPeople with chronic diseases experience barriers to managing their diseases and accessing available health services. Patient navigator programs are increasingly being used to help people with chronic diseases navigate and access health services.ObjectiveThe objective of this review was to summarize the evidence for patient navigator programs in people with a broad range of chronic diseases, compared to usual care.MethodsWe searched MEDLINE, EMBASE, CENTRAL, CINAHL, PsycINFO, and Social Work Abstracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
311
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(313 citation statements)
references
References 101 publications
2
311
0
Order By: Relevance
“…The ability of the TN to proactively reach out to vulnerable patients who have been missing important medical appointments takes into account the developmental factors and multiple life transitions occurring in emerging adulthood and may have contributed to the reengagement of the four patients in the post‐TN cohort. Similar patient navigation approaches have proven successful in other high‐risk populations . This study outlines the potential impact a TN can have on engagement in care for the hemoglobinopathy population.…”
Section: Discussionmentioning
confidence: 94%
“…The ability of the TN to proactively reach out to vulnerable patients who have been missing important medical appointments takes into account the developmental factors and multiple life transitions occurring in emerging adulthood and may have contributed to the reengagement of the four patients in the post‐TN cohort. Similar patient navigation approaches have proven successful in other high‐risk populations . This study outlines the potential impact a TN can have on engagement in care for the hemoglobinopathy population.…”
Section: Discussionmentioning
confidence: 94%
“…Several systematic reviews of PN have been published and have shown that PN improves clinical outcomes for a variety of chronic diseases . Some reviews have included only certain subgroups such as the elderly with cancer or have been limited to English‐speaking patients .…”
Section: Introductionmentioning
confidence: 99%
“…11 Several systematic reviews of PN have been published and have shown that PN improves clinical outcomes for a variety of chronic diseases. 12,13 Some reviews have included only certain subgroups such as the elderly with cancer 14 or have been limited to English-speaking patients. 15 PN was shown to have early success in helping with the accrual of minorities to clinical trials by increasing awareness and access and reducing barriers to participation.…”
Section: Introductionmentioning
confidence: 99%
“…13 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) supportive, for example in providing information and reassurance during treatment, was patient, and clear in communication. Furthermore, they indicated that the contact with the FN was pleasant because they were personal and showed empathy.…”
Section: Fns Guided Patients Through Fp Processmentioning
confidence: 99%